Mindfulness and the 'psychological imagination'. Issue 5 (16th April 2020) - Nehring, Daniel; Frawley, Ashley
Abstract: We analyse the rise of 'mindfulness' in English language media discourses and contextualise it in terms of its expression of a persistent underlying 'psychological imagination' in contemporary thinking about social problems. An inversion of C. Wright Mills' much‐cited sociological imagination, the psychological imagination draws on medical‐scientific authority to treat social problems as private concerns rooted in individual biology, mentality and behaviour. We analyse the roles which academic claims‐making, commercial interests and mass mediatisation have played in the rise of mindfulness from the late 1970s onwards. We first map the translation of mindfulness from Buddhist philosophy into Western psychotherapy and popular psychology before considering its emergence and expression in the public sphere of news media claims‐making. We argue that where the sociological imagination 'promised' above all the treatment of private troubles as public issues and insights into the 'human variety' produced by myriad ways of living, the psychological imagination promises the isolation of public issues as private concerns rooted in individual biology, mentality and behaviour. The psychological imagination permeates the expression of mindfulness as a solution to social ills and symbolises the comparative decline of assumptions implicit in Mills' 20th century rousing call to social scientists.